EKSPLORASI DAN KARAKTERISASI BAKTERI POTENSIAL PENGHASIL SENYAWA ANTIFOULING YANG BERASOSIASI DENGAN ALGA COKLAT (PHAEOPHYTA) DI PERAIRAN KEPULAUAN KARIMUNJAWA JEPARA - Barri Pratama; Endang Kusdiyantini; Agung Suprihadi; Anto Budiharjo; AB Susanto (Jurnal Akademika Biologi, 2014)
Biofouling is a settlement process from marine organisms initiated by biofilm (microbial layers). Corrosion on the vessels, pipelines under the sea, oil plants, etc are big problems in the industrial today cause adversely affects. Antifouling paints have been developed to prevent settlement of organisms, however antifouling paints contain heavy metals and biocides which have toxic effects on marine ecosystems. Antifouling compound which environmental friendly is a solution for one of the paint component. The aim of this research was to isolate bacteria associated with brown algae which had potential to produce antifouling compound from Karimunjawa islands, Jepara.Isolate KS1-1 showed antifouling activity against Pseudomonas aeruginosa as biofilm-forming bacteria.This isolate had been characterized in morphology, moleculer and biochemichal identification.Moleculer analyses of 16S rRNA sequence, KS1-1 showed similarity 94% from 287 bp with Vibrio sp. W-137-16S ribosomal RNA gene, partial sequence. Keywords : Antifouling, Phaeophyta,Biofouling, 16S rRNA, Vibrio